Global, Regional, and National Burden of Endometrial Cancer, 1990–2017: Results From the Global Burden of Disease Study, 2017 - Zhang, Shuang; Gong, Ting-Ting; Liu, Fang-Hua; Jiang, Yu-Ting; Sun, Hui; Ma, Xiao-Xin; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Oncology, 2019)
Endometrial cancer (EC) is the most common malignancy affecting women in developed countries. Recently, the EC disease burden has changed; therefore, the Global Burden of Disease (GBD ) 2017 was used to comprehensively analyze the global, regional, and national burden of EC between 1990 and 2017. General GBD cancer estimation methods were used with the data input from vital registration systems and cancer registries. Annual percent changes were calculated to quantify the trends of EC burden estimates during the study period. Furthermore, the sociodemographic index (SDI) was used to assess the relationship between the EC burden estimates and development level. From 1990 to 2017, the age-standardized incidence and prevalence rate of EC increased globally by 0.58% and 0.89% per year, respectively. In contrast, the age-standardized death rate and disability-adjusted-life years (DALYs) decreased by 1.19% and 1.21% per year, respectively. Increasing trends in both the incidence and prevalence were observed in all SDI quintiles, except for the low SDI quintiles, whereas decreasing trends were observed in all SDI quintiles for mortality and DALYs. Additionally, a non-linear association existed for the level of mortality rate, DALYs, and SDI. Of note, there was a strong positive association between a high body mass index and DALYs across all SDI quintiles. In conclusion, EC incidence and prevalence rates are growing globally, whereas the death rate and DALYs decreased between 1990 and 2017. Greater efforts, particularly detailed prevention strategies for reducing obesity, should be performed to reverse this phenomenon.